Freedom roots : histories from the Caribbean - Dubois, Laurent, 1971-; Turits, Richard Lee (University of North Carolina Press, 2019)
For centuries, the Caribbean has been centered in the crosscurrents of global transformations. From the emergence of racial slavery and plantation agriculture to foreign military occupation and radical interventions, the Atlantic world has been deeply shaped by European and U.S. imperialism. But the Caribbean is also a place where people - through contestation, innovation, global migration, and some of history's most dramatic revolutions - have created alternatives to those imposed by their rulers. --